2015
DOI: 10.1007/8904_2015_471
|View full text |Cite
|
Sign up to set email alerts
|

News on Clinical Details and Treatment in PGM1-CDG

Abstract: Phosphoglucomutase 1 deficiency has recently been reported as a novel disease that belongs to two different classes of metabolic disorders, congenital disorders of glycosylation (CDG) and glycogen storage diseases.This paper focuses on previously reported siblings with short stature, hypothyroidism, increased transaminases, and, in one of them, dilated cardiomyopathy (DCM). An intronic point mutation in the PGM1-gene (c.1145-222 G>T) leads to a complex alternative splicing pattern and to almost complete absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…20,22 In PGM1-CDG (MIM 614921), a disorder with characteristics of both glycogenosis and CDG, galactose supplementation was shown to improve glycosylation as well as clinical presentation. 23,24 Galactose substitution is also a treatment option for SLC35A2-CDG. This disorder resembles clinically SLC39A8 deficiency with encephalopathy (epilepsy, severe psychomotor disability, blindness, cerebral atrophy) and dysmorphism.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 In PGM1-CDG (MIM 614921), a disorder with characteristics of both glycogenosis and CDG, galactose supplementation was shown to improve glycosylation as well as clinical presentation. 23,24 Galactose substitution is also a treatment option for SLC35A2-CDG. This disorder resembles clinically SLC39A8 deficiency with encephalopathy (epilepsy, severe psychomotor disability, blindness, cerebral atrophy) and dysmorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in some unknown way, galactose supports the ER related glycosylation as well in PGM1 deficiency, where it has been shown that lipid linked oligosaccharide synthesis is arrested, but recovers on in vitro galactose treatment [ 24 , 25 , 26 ]. Galactose might offer extra energy substrate for patients, since some of the adults with PGM1 deficiency also show an improvement of their muscle disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the PGM1 mutations cause HH due to the decreased threshold for glucose-mediated insulin release from the pancreatic cells (131). A later report (132) on two of the patients from the publication by Tegtmeyer (128) has shown more pronounced hypoglycosylation in childhood than in adults with a total PGM1-mRNA level reduced to 0.25% of that of normal controls. The study has also reported that hypoglycaemia might occur in PGM1 deficient patients by starving and would be exaggerated by strong exercise (132).…”
Section: Chi Due To Abnormalities In Metabolic Pathwaysmentioning
confidence: 95%